2008
DOI: 10.1089/ten.tea.2007.0305
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Gel as an In Situ–Forming Scaffold for Rat Bone Marrow Mesenchymal Stem Cells In Vivo

Abstract: We herein formulated and characterized an in situ-forming chitosan gel consisting of chitosan and glycerol phosphate (GP) disodium salt, and examined its use as an in vivo scaffold for rat bone marrow mesenchymal stem cells (rBMSCs). First, the phase transition behaviors of chitosan solutions formulated with and without GP were characterized as a function of temperature. Chitosan solutions containing > 20 wt % GP became a gel at 37 degrees C and maintained this form for 28 days in vitro and in vivo. Next, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…Recent studies have shown that the addition of glycerol phosphate disodium salt (GP) to CTS makes it possible to obtain a liquid solution at room temperature (RT). By means of the body temperature, this injectable solution undergoes a phase transition and becomes a gel (28,29). This behavior was observed to be related to electrostatic interactions between positively charged amine groups of CTS and phosphate anions of GP (29).…”
Section: Originalmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent studies have shown that the addition of glycerol phosphate disodium salt (GP) to CTS makes it possible to obtain a liquid solution at room temperature (RT). By means of the body temperature, this injectable solution undergoes a phase transition and becomes a gel (28,29). This behavior was observed to be related to electrostatic interactions between positively charged amine groups of CTS and phosphate anions of GP (29).…”
Section: Originalmentioning
confidence: 97%
“…Chitosan scaffolds preparation CTS scaffolds were prepared as described elsewhere (28,29). In brief, a CTS solution was obtained by dissolving the polymer in 0.1 M acetic acid solution prepared in deionized water (DW) at a final concentration of 2.2% w/v (polymer/solvent) and sterilized by autoclave.…”
Section: Osteogenic Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…A chitosan/glycerophosphate salt formulation was prepared as a biocompatible injectable vehicle for mesenchymal stem cells (MSCs) delivery [4]. Chitosan (CS) is a promising biocompatible and biodegradable natural biomaterial, while glycerophosphate salts are well-known biocompatible agents; the formulations based on chitosan combinations can be held liquid at room temperature for encapsulating living cells and turn into hydrogel in situ at body temperature [5].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, CS solutions containingβ-GP can remain in solution at low temperature and become a networked, structural solid at physiological pH and body temperature in the form of injectable, thermosensitive hydrogel [14][15][16] . CS/β-GP thermosensitive hydrogel also has biocompatiblity and biodegradability, and could stimulate the proliferation of MSCs where drugs, growth factors, and cells can be incorporated into the hydrogel before solidification in situ [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%